Research of the Parameter Comprehensive Optimization of Excavator Working Device based on the Hybrid Optimization Algorithm - Zhang Xian; Liu Baixi; Qu Tao (Jixie chuandong, 2016)
In order to optimize the performance of excavator in the specific region,The mathematical model of optimization design is obtained constrained by operating performance and mechanical property of the working device. The parameter of working device in the anti shovel hydraulic excavator are integrated optimized by using the hybrid algorithm of simulated annealing and penalty function. The efficiency and accuracy of the solution is improved for the advantages of two algorithms are effectively combined and local optimal solution is avoided. The optimization and simulation of the working device are realized by using the Matlab programming,the defects of the original design are corrected and the performance of the whole machine is greatly improved.